Key Performance Indicator (KPI) Design of Bamboo Creative Industry in Godean Sleman District Area - Zabidi, Yasrin (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Performance issues are not only important for upper middle and large companies, but also important for Small and Medium Industries Creative Industries. To evaluate the current condition of a creative industry, the creative industry needs to determine the multi-criteria Key Performance Indicator (KPI) properly and correctly. Therefore in this study, researchers tried to design a Key Performance Indicator (KPI) for the creative industries of bamboo crafts in the Godean district of Sleman. The design of KPI uses the Balanced Scorecard method which includes setting strategic objectives, determining key performance indicators (KPI). From the results of the study obtained 10 KPI, namely: the level of sales growth, the level of customer growth, the level of customer satisfaction, the level of customer complaint fulfillment, the level of production speed, the number of products produced by labor, the percentage of defective products, the percentage of the level of effort to repair defective products, the level of productivity employees, and employee job satisfaction Keywords: Performance, Performance Indicator, Key Performance Indicator, Balanced Scorecard, Creative Industry.